Eph receptors and ephrin signaling pathways: a role in bone homeostasis. - Edwards, C; Mundy, G (2008)
The maintenance of bone homeostasis is tightly controlled, and largely dependent upon cellular communication between osteoclasts and osteoblasts, and the coupling of bone resorption to bone formation. This tight coupling is essential for the correct function and maintenance of the skeletal system, repairing microscopic skeletal damage and replacing aged bone. A range of pathologic diseases, including osteoporosis and cancer-induced bone disease, disrupt this coupling and cause subsequent alterations in bone homeostasis. Eph receptors and their associated ligands, ephrins, play critical roles in a number of cellular processes including immune regulation, neuronal development and cancer metastasis. Eph receptors are also expressed by cells found within the bone marrow microenvironment, including osteoclasts and osteoblasts, and there is increasing evidence to implicate this family of receptors in the control of normal and pathological bone remodeling.